Attack Surface Score for Software Systems - Yudeep Rajbhandari; Rokin Maharjan; Sakshi Shrestha; Tomas Cerny (Future Internet, 2025)
Software attack surfaces define the external boundaries—entry points, communication channels, and sensitive data stores through which adversaries may compromise a system. This paper introduces a scoring mechanism that produces a normalized attack-surface metric in the range of 0–1. Building on the established Damage-Potential-to-Effort ratio, our approach further incorporates real-world vulnerability intelligence drawn from MITRE’s CVE and CWE repositories. We compute each application’s score by ingesting preliminary findings from a static-analysis tool and processing them through our unified model. To assess effectiveness, we validate the scoring system across a spectrum of scenarios, from a simple Java application to complex enterprise applications. The resulting metric offers development and security teams a concise, objective measure to monitor an application’s attack surface and hence proactively identify vulnerabilities in their applications. This tool can also be used to benchmark various third-party or dependent applications, enabling both developers and security practitioners to better manage risk.